CREATIVE MEDIA WORKERS AS REPRESENTATIVES TO ACTUALIZE THE TAGLINE OF “INDEPENDENT DAN TRUSTED” - patricia robin (Mediakom, 2020)
Mass media workers have a good ability to convey ideas to be enjoyed by a wide and heterogeneous audience. Their talents and interests are not arbitrary. They have taken special education in college and graduated with a related bachelor's degree. However, their intellectual abilities are not accompanied by the ability to appreciate and reward themselves, which should deserve a decent income or a comfortable working environment. In the name of capitalism which was finally realized in the form of alienation, they carried out the work with great pride even though it was apparent. This study uses qualitative research methods by collecting data through interviews of one of the televisions workers. Based on the research results, it is clearly illustrated how the mass media workers consider that completely devoting themselves to companies that have provided opportunities and income is something that is worth doing. Moreover, there is special pride when they are able to contribute in providing education and information to the wider community. This confirms false awareness that arises from a mass media worker. Kata Kunci: Buruh Kreatif Media massa, Ekonomi Politik Media, Kapitalisme, Alienasi